Regarding "I Am Not Captain Dunsel!" (Fall 2009) - Steven J. Bell (Issues in Science and Technology Librarianship)
A letter to the editor is presented in response to the comment of Susanne J. Redalje to the article "It Was Nice Known' Ya Special Branch Library," by Steven J. Bell, in the October 2: 2009 issue of "LJ Newswire."